2022
DOI: 10.3389/fenvs.2022.896892
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Environmental Regulation on High-Quality Economic Development

Abstract: Based on the connotation of high-quality economic development (HQED) in China, this study uses panel data of 30 provinces (cities and regions) in China from 2005 to 2019 to construct an evaluation index system of HQED with three dimensions of “economic development—social life—ecological environment,” and establishes a fuzzy comprehensive evaluation model to calculate the HQED index. The results show that the high-quality development level of China’s economy shows an upward trend of fluctuation, but the develop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 17 publications
0
10
0
Order By: Relevance
“…And systematic environmental regulation (ER) will surely become the core tool to achieve the targets (Lyu et al, 2020 ). ER tools in China have long been dominated by command-and-control environmental regulation (CMCER), which is effective (Wang & Liu, 2022 ; Zeng et al, 2022 ) but may lead to negative economic and social effects (e.g., inhibiting the foreign direct investment (Chen et al, 2022 ), industrial growth (Liu et al, 2021 ), and economic quantity growth (Ma & Xu, 2022 )). In order to direct enterprises to protect the environment, China has been advocating implementing market-based environmental regulation (MBER) in the past few years (Ren et al, 2020 ; Song & Han, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…And systematic environmental regulation (ER) will surely become the core tool to achieve the targets (Lyu et al, 2020 ). ER tools in China have long been dominated by command-and-control environmental regulation (CMCER), which is effective (Wang & Liu, 2022 ; Zeng et al, 2022 ) but may lead to negative economic and social effects (e.g., inhibiting the foreign direct investment (Chen et al, 2022 ), industrial growth (Liu et al, 2021 ), and economic quantity growth (Ma & Xu, 2022 )). In order to direct enterprises to protect the environment, China has been advocating implementing market-based environmental regulation (MBER) in the past few years (Ren et al, 2020 ; Song & Han, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, some studies have found that environmental regulation policies may greatly promote the level of green and high-quality economic development (Chen et al, 2020). Some papers suggest that environmental regulation has a nonlinear influence on green innovation (Liu et al, 2022) and the development of green economy (Shuai and Fan, 2020;Wang, 2020;Ma and Xu, 2022). And some scholars pointed out that the implementation of environmental regulations will bring spatial spillover effects to high-quality economic development in adjacent areas (Feng and Chen, 2018).…”
Section: Research On Green Creditmentioning
confidence: 99%
“…Yang et al (2019) discussed the role of the government in high-quality innovation development, and pointed out that government governance needs to be adapted to local conditions. In the case of environmental governance, the impact of environmental regulations varies for different regions (Ma and Xu, 2022). Appropriate environmental regulations can promote high-quality and sustainable economic development (L. Chen et al, 2022a), but overly stringent regulatory measures can be counterproductive (Yang et al, 2022).…”
Section: Introductionmentioning
confidence: 99%